2022
DOI: 10.3390/cimb44100299
|View full text |Cite
|
Sign up to set email alerts
|

Trio-Drug Combination of Sodium Valproate, Baclofen and Thymoquinone Exhibits Synergistic Anticonvulsant Effects in Rats and Neuro-Protective Effects in HEK-293 Cells

Abstract: Epilepsy is a chronic brain disorder, with anti-epileptic drugs (AEDs) providing relief from hyper-excitability of neurons, but largely failing to restrain neurodegeneration. We investigated a progressive preclinical trial in rats, whereby the test drugs; sodium valproate (SVP; 150 and 300 mg/kg), baclofen (BFN; 5 and 10 mg/kg), and thymoquinone (THQ; 40 and 80 mg/kg) were administered (i.p, once/day for 15 days) alone, and as low dose combinations, and subsequently tested for antiseizure and neuroprotective p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 93 publications
0
5
0
Order By: Relevance
“…After SCI, an inhibitory microenvironment is formed in the lesion area, and adult neurons exhibit poor intrinsic growth potential [ 23 , 24 ]. After SCI, autophagic flux is impaired, and the accumulation of a large number of oxidative stress products accelerates apoptosis [ 10 , 11 ]. Furthermore, Cx43 has been shown to protect embryos from reactive oxygen species (ROS)-induced autophagic stress and apoptosis to ensure the maintenance of mitochondrial membrane potential and ATP production, while baclofen can promote protective autophagy by downregulating Cx43 expression on cell and mitochondrial membranes [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After SCI, an inhibitory microenvironment is formed in the lesion area, and adult neurons exhibit poor intrinsic growth potential [ 23 , 24 ]. After SCI, autophagic flux is impaired, and the accumulation of a large number of oxidative stress products accelerates apoptosis [ 10 , 11 ]. Furthermore, Cx43 has been shown to protect embryos from reactive oxygen species (ROS)-induced autophagic stress and apoptosis to ensure the maintenance of mitochondrial membrane potential and ATP production, while baclofen can promote protective autophagy by downregulating Cx43 expression on cell and mitochondrial membranes [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Autophagic flux is impaired after SCI, and the dynamic balance of autophagic flow is disrupted, leading to autophagy stress and the accumulation of numerous oxidative stress products to accelerate cell apoptosis [ 9 ]. Recent studies have demonstrated that gap junction protein 43 (connexin43, Cx43) protects embryos from reactive oxygen species (ROS)-induced autophagic stress and apoptosis, maintaining the mitochondrial membrane potential and production of ATP [ 10 ], while baclofen can enhance protective autophagy [ 11 ] by downregulating the expression of Cx43 on cells and mitochondrial surfaces. These findings indicate that Cx43 regulates autophagy during oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…The Insilco results revealed that trio-drug combination binds the Akt active site as a supramolecular complex, which could have served as a delivery system that affects the penetration and the binding to the new target [61] Abbreviations: AKT, protein kinase B; BFN, baclofen; Htf, human transferrin; mTOR, mammalian target of rapamycin; PHT, phenytoin; SERT, serotonin reuptake transporter; SVP, sodium valproate.…”
Section: Epilepsymentioning
confidence: 99%
“…Furthermore, BLF showed an anti-convulsant effect in pentylenetetrazol-induced model of epilepsy in developing rats of 7, 12, 18, and 25 days ( Kubová et al, 1996 ). In adult rats, BLF reduced pentylenetetrazol-induced seizures ( Chen et al, 2004 ) and electroshock-induced seizures ( Hyder Pottoo et al, 2022 ). Similarly, BLF reduced seizures in a mouse pentylenetetrazole kindling model of epilepsy ( De Sarro et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%